2015
DOI: 10.1039/c5tc02795k
|View full text |Cite
|
Sign up to set email alerts
|

The design of a ceramic phosphor plate with functional materials for application in high power LEDs

Abstract: Here we report the design of a ceramic phosphor plate made up of different functional materials, such as SiO2 and MgO, and Lu3Al5O12:Ce3+ (LuAG:Ce) for the fabrication of remote phosphors in high-power LED applications.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
12
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 39 publications
(12 citation statements)
references
References 15 publications
0
12
0
Order By: Relevance
“…Compared to single crystals, polycrystalline ceramics allow for a controllable microstructure (such as pores, secondary phases, grain boundaries, and grain sizes) and offer great freedom in controlling the light scattering and absorption processes . Moreover, phosphor ceramics possess outstanding characteristics such as high thermal conductivity, superior mechanical strength, and excellent chemical and physical stability . Ji et al.…”
Section: Survey Of Laser Phosphorsmentioning
confidence: 99%
See 1 more Smart Citation
“…Compared to single crystals, polycrystalline ceramics allow for a controllable microstructure (such as pores, secondary phases, grain boundaries, and grain sizes) and offer great freedom in controlling the light scattering and absorption processes . Moreover, phosphor ceramics possess outstanding characteristics such as high thermal conductivity, superior mechanical strength, and excellent chemical and physical stability . Ji et al.…”
Section: Survey Of Laser Phosphorsmentioning
confidence: 99%
“…Ji et al. addressed that the green‐emitting LuAG:Ce phosphor ceramic had a smaller thermal quenching and a higher thermal conductivity (4–5 W m −1 K −1 ) than the parent powder . Tang et al.…”
Section: Survey Of Laser Phosphorsmentioning
confidence: 99%
“…Indeed, it has been demonstrated that thermal conductivity is almost eight times larger in ceramic phosphor than their parent powder phosphor. This characteristic helps dissipate heat and reduce thermal quenching . In addition, it presents higher fracture toughness than glass ceramic and glasses used for the phosphor in glass (PIG) approaches.…”
Section: Introductionmentioning
confidence: 99%
“…29 To improve the required characteristics of the PCP, other materials can be added to the raw materials during the synthesis process. Ji et al 30 and Lee et al 31 in which two phosphor crystals with green and red emission bands were present. They reported that the use of the CaO-SiO 2 system as the host glass obtained a PGP having broad emission bands for good color rendering.…”
Section: Types and Characteristics Of Phosphor Platesmentioning
confidence: 99%